2022
DOI: 10.3390/cancers14112665
|View full text |Cite
|
Sign up to set email alerts
|

Ficus dubia Latex Extract Induces Cell Cycle Arrest and Apoptosis by Regulating the NF-κB Pathway in Inflammatory Human Colorectal Cancer Cell Lines

Abstract: Colorectal cancer is one of the most diagnosed cancers that is associated with inflammation. Ficus dubia latex is recognized as a remedy with various therapeutic effects in traditional medicine, including anti-inflammatory and antioxidant activity. The present study aims to compare the anti-tumor activity of Ficus dubia latex extract (FDLE) against HCT-116 and HT-29 human colorectal cancer cell lines in normal and inflammatory condition and explore its mechanism of action. FDLE exhibited remarkable antiprolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…NF-κB is a major link between inflammation and cancer; thus, it plays a crucial role in colorectal cancer occurrence and development through its mediated transcription. NF-κB signaling activation promotes the establishment of a pro-inflammatory tumor microenvironment in colorectal cancer cells and regulates cell proliferation, apoptosis, metastasis, angiogenesis, drug resistance, and inflammation-related target gene expression ( Hu et al, 2022 ). Simultaneously, NF-κB is a major anti-apoptotic factor.…”
Section: Introductionmentioning
confidence: 99%
“…NF-κB is a major link between inflammation and cancer; thus, it plays a crucial role in colorectal cancer occurrence and development through its mediated transcription. NF-κB signaling activation promotes the establishment of a pro-inflammatory tumor microenvironment in colorectal cancer cells and regulates cell proliferation, apoptosis, metastasis, angiogenesis, drug resistance, and inflammation-related target gene expression ( Hu et al, 2022 ). Simultaneously, NF-κB is a major anti-apoptotic factor.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the root ethanolic extract displays potent antidiabetic effects through the inhibition of α-glucosidase, one of the drug targets for diabetes, and anticancer activity against lung- and ovarian-cancer cell lines with genome-safe [ 31 ]. Moreover, it was found that the latex extract has the potential for the prevention and treatment of human colorectal cancer through the regulation of the inflammatory pathway [ 33 , 34 ]. Although FL has been reported to have the potential against inflammation and diabetes, there is no scientific information of its bioactive compounds and biological activity on inflammation-associated adipocyte dysfunction, which is a major cause of insulin resistance and diabetes (T2DM).…”
Section: Introductionmentioning
confidence: 99%